Chinese cross-cultural adaptation and validation of the Well-being Numerical Rating Scales - Luo, Qing; Liu, Chunqin; Zhou, Ying; Zou, Xiaofang; Song, Liqin; Wang, Zihan; Feng, Xue; Tan, Wenying; Chen, Jiani; Smith, Graeme D.; Chiesi, Francesca (Frontiers in Psychiatry, 2023)
Well-being is a multi-domain concept that involves measuring the physical, psychological, social, and spiritual domains. However, there are currently few multi-domain and comprehensive well-being instruments available. In addition, measures that do exist customarily contain a vast number of items, that may lead to boredom or fatigue in participants. The Well-being Numerical Rating Scales (WB-NRSs) offers a concise and multi-domain well-being scale. This study aimed to perform the translation, adaptation and validation of the Chinese version of WB-NRSs(WB-NRSs-CV). A total of 639 clinical participants and 542 community participants completed the WB-NRSs-CV, the Single-item Self-report Subjective Well-being Scale (SISRSWBS), the World Health Organization Five-item Well-Being Index (WHO-5), the 10-item Perceived Stress Scale (PSS-10) and the Kessler Psychological Distress Scale(K10). High internal consistency and test-retest reliability was obtained for both two samples. Additionally, WB-NRSs-CV was positively associated with SISRSWBS and WHO-5, and negatively associated with PSS-10 and K10. In the Item Response Theory Analysis, the model fit was adequate, with the discrimination parameters ranging from 2.73 to 3.56. The difficulty parameters ranged from -3.40 to 1.71 and were evenly spaced along the trait, attesting to the appropriateness of the response categories. The invariance tests demonstrated that the WB-NRSs-CV didn't differ across groups by gender and age. These evidences supported that the WB-NRSs-CV was translated appropriately and cross-culturally adapted in China. It can be used as a rapid and relevant instrument to assess well-being in both clinical and non-clinical settings, with utility for well-being measurement and management in Chinese people.